Federal cloud computing : the definitive guide for cloud service providers - Metheny, Matthew (Elsevier/Syngress, 2012)
"In recent years 'cloud computing' has emerged as a model for providing IT infrastructure, resources and services that has the potential to drive significant value to organizations through increased IT efficiency, agility and innovation. However, Federal agencies who were early adopters of cloud computing have learned that there are many challenges and risks that must be addressed in order to realize these benefits"--